2021
DOI: 10.3390/genes12122029
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Theragnostic Relationship between Chemotherapeutic Resistance, and Sensitivity and miRNA Expressions in Head and Neck Cancers: A Systematic Review and Meta-Analysis Protocol

Abstract: Background: The microRNAs (miRNAs) are small noncoding single-stranded RNAs typically 19–25 nucleotides long and regulated by cellular and epigenetic factors. These miRNAs plays important part in several pathways necessary for cancer development, an altered miRNA expression can be oncogenic or tumor-suppressive. Recent experimental results on miRNA have illuminated a different perspective of the molecular pathogenesis of head and neck cancers. Regulation of miRNA can have a detrimental effect on the efficacy o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…This drug resistance tends to lead to rapid deterioration of the long-term prognosis of the patient [ 25 , 57 ]. This study aims to evaluate the potential role of miRNAs, which are one type among several types of small non-coding RNAs known to play a specific role in cancer progression, including the development of chemoresistance [ 25 , 33 ]. The regulation of chemoresistance specific miRNA is significant in the genesis of cancer as well as in the prognosis of the affected patient.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This drug resistance tends to lead to rapid deterioration of the long-term prognosis of the patient [ 25 , 57 ]. This study aims to evaluate the potential role of miRNAs, which are one type among several types of small non-coding RNAs known to play a specific role in cancer progression, including the development of chemoresistance [ 25 , 33 ]. The regulation of chemoresistance specific miRNA is significant in the genesis of cancer as well as in the prognosis of the affected patient.…”
Section: Discussionmentioning
confidence: 99%
“…The study was conducted by the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) statement [ 32 ] and was completed following a previously established protocol (PROSPERO registration number: CRD42018104657). The study protocol was already published elsewhere [ 33 ].…”
Section: Search Strategy and Methodsmentioning
confidence: 99%
“…Many reviews of miRNA expression among oral cancers have identified the potential utility of miRNA expression profiles as biomarkers and determinants for chemotherapy treatment [ 8 , 9 ]. This has led to the identification of specific miRNAs that modulate multiple tumorigenesis pathways, as well as resistance to chemotherapeutic agents—such as miR-21 and chemoresistance to Cisplatin therapy [ 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…They seem to have a role in cervical carcinogenesis. Many articles covering the topic of CC discuss a single type of miRNA and its specific role [ 6 , 37 , 38 , 39 , 40 , 41 ]. They elaborate on how the respective miRNA causes resistance or sensitivity and the mechanism involved with decrease or increase in the chemoresistance of a specific anti-cancer drug.…”
Section: Introductionmentioning
confidence: 99%